Use of Infrared Thermography under Laboratory Conditions - Suchanek, Andrej; Loulova, Maria; Harusinec, Jozef; Strazovec, Peter (Manufacturing Technology Journal, 2018)
The article deals with the use of thermography for the detection of the course of temperature fields during braking. Substantially higher demands on the reliability and safety of individual parts of the braking system are required with the increasing speed of rail vehicles. The noise parameter is also important in addition to the safety itself. Noise arises due to braking by brake with cast iron blocks. One of the possibilities of reducing noise is the use of composite materials for the production of brake blocks. A higher friction coefficient is a disadvantage of the use of brake blocks made of composite materials. These are much worse heat conductors than cast iron blocks. This causes damage to the tread of the railway wheel. The use of infrared thermography is one way of detecting thermal fields. It is a method that allows a non-contacting way to display, measure and analyze a temperature field on the surface body.
Keywords: Thermography; Thermogram; Thermal Camera; Braking; Brake block; Emissivity